2023
DOI: 10.1021/acs.jpcc.2c08695
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-Like Water in the NU-1000 Zr-MOF: A Molecular Level Understanding of Balanced Hydrophobicity in Humid Conditions

Abstract: While the structural features and tunability of metal−organic frameworks (MOFs) make them promising materials for chemical warfare agent (CWA) hydrolysis, their stability and performance in conditions of varying humidity is an unsolved challenge. Understanding what design rules enable lasting hydrolytic functionality in evolving field conditions is consequently essential to developing practical MOFs for such applications. In this work, molecular dynamics simulations are carried out to examine the behavior of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Beyond ρ wat ≈ 0.3 g/g, the hexagonal mesopore becomes preferable to a triangular micropore (Figure S37). These sittings are consistent with a prior simulation study using a different force field …”
Section: Resultsmentioning
confidence: 99%
“…Beyond ρ wat ≈ 0.3 g/g, the hexagonal mesopore becomes preferable to a triangular micropore (Figure S37). These sittings are consistent with a prior simulation study using a different force field …”
Section: Resultsmentioning
confidence: 99%
“…The more hydrophilic the material, the more water-framework interactions will precede interactions with target species, lowering active site accessibilities and target species reaction rates. These obstacles make hydrophilic MOFs a poor choice for chemical reaction applications in settings with large atmospheric moisture levels [15]. Hydrophobic MOFs show promise in this regard, as their resistance to chemical degradation by water [62] makes them chemically stable in humid conditions and unrestricted by competitive adsorption upon water exposure [63].…”
Section: Hydrophilicity and Hydrophobicitymentioning
confidence: 99%
“…Establishing a perfect balance of stability, topology, and water affinity that diminishes these challenges would be a major stride in developing ideal MOFs for the given application. This was the focus behind our recent publication, where we investigated the behavior of environmental water at various loadings in NU-1000 [15], a Zr-MOF with combined features of strong node-linker bonds, large pore volumes, and internal hydrophobicity. Computational results demonstrated that water in NU-1000 exhibits a structural phase somewhere between liquid and vapor.…”
Section: Hydrophilicity and Hydrophobicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The method’s development included measurements of the capacity of the Zr-MOF NU-1000 and nonimpregnated AC to adsorb and degrade GB under both dry and humid conditions. NU-1000 is a promising Zr-MOF with large pores, whose ability to adsorb and degrade OP-agents has been studied previously. ,,, …”
Section: Introductionmentioning
confidence: 99%